Cross-layer Throughput Optimization in Slow Fading Wireless Channel - Velickovic, Z. S.; Jevtovic, M.; Pavlovic, V. (Elektronika ir Elektrotechnika, 2013)
In this paper the optimizing cross-layer algorithm is presented which minimizes long-term average packet dropping subject to an average transmission power of single user wireless channel. The optimization problem is defined as Markov decision process (MDP) and the composite state space of the communication system with transition matrices of probabilities is determined. The structure of the obtained optimal policies for Rayleigh and independent and identically distributed (i.i.d.) fading channel is taken into consideration. Simulation results confirm that the proposed cross-layer algorithm provides adaptation of network parameters and makes it possible for satisfying QoS in a wide range according to application demands. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.2302